Primary hydatid cyst of pancreas: Case report and review of literature. (2016) - Ahmed, Zeeshan; Chhabra, Sanjeev; Massey, Ashish; Vij, Vikesh; Yadav, Rahul; Bugalia, Rajendra; Kankaria, Jeevan; Jenaw, Raj K.
Highlights: Pancreatic hydatid cysts are very rare entities with an incidence ranging from 0.14% to 2%. They can masquerade as pseudocyst or cystic neoplasm of pancreas. Ultrasonography, Computed tomography and Hydatid serology help in diagnosis. Pericystectomy, Partial cystectomy with omentopexy/external drainage, Marsupialization, Cysto-enterostomy are some of the surgical options. Prophylactic preoperative and postoperative anti-helminthics(Albendazole) are recommended. Abstract: Introduction: Hydatid disease is caused by the larval stage of Echinococcus granulosus. It most commonly affects the liver and lung. Pancreatic hydatid cyst (PHC) is very rare with incidence of 0.14%–2%. Presentation of case: A 40 year old lady presented with epigastric pain for last 3 months. A 5 × 5 cm abdominal lump occupying the epigastric and left hypochondrial region was noted on physical examination. Ultrasonography (USG) and Contrast enhanced Computed Tomogrpahy (CT) revealed a 55 × 57 mm cystic structure in the pancreatic body. Endoscopic ultrasound guided fluid aspiration cytology revealed normal Carcinoembryonic antigen and Amylase levels. Cytological examination was noncontributory. During open surgical exploration, it was found to be a hydatid cyst. After irrigation with scolicidal agent and evacuation of cystic contents, Partial cystectomy with external drainage was done. Histopathological biopsy revealed Hydatid cyst. Post-operative ELISA (Enzyme linked immunosorbent assay) for Echinococcal antigen was positive. Discussion: PHC is a rare entity. Most common mode of spread is hematogenous. Cysts in pancreatic head can present as obstructive jaundice. Cysts in body and tail are usually asymptomatic. USG, CT and Hydaitd serology can help in diagnosis and monitoring recurrence. Surgical exploration is treatment of choice. Options include pericystectomy, partial cystectomy +/− external drainage/omentopexy, marsupialization or cysto-enterostomy. Preoperative and Post-operative anti helminthic (Albendazole) is recommended. Conclusion: PHC can masquerade as pseudocyst or cystic neoplasm of pancreas. It should always be considered in the differential diagnosis of cystic pancreatic lesion in patients from endemic regions.